1990
DOI: 10.1136/jnnp.53.11.994
|View full text |Cite
|
Sign up to set email alerts
|

Shy-Drager syndrome. Effect of fludrocortisone and L-threo-3,4-dihydroxyphenylserine on the blood pressure and regional cerebral blood flow.

Abstract: In nine cases of Shy-Drager syndrome, the changes in blood pressure and cerebral blood flow on sitting up from a supine position were studied. The influence of fludrocortisone, a synthetic mineralocorticoid, and L-threo-3,4-dihydroxyphenylserine (DOPS), a precursor of norepinephrine, on these changes was examined. On After the initial set of measurements, seven patients were treated with fludrocortisone for two weeks. The fludrocortisone was administered in the morning orally at a daily dose of 0-2 mg in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
10
3
Order By: Relevance
“…Cerebral blood flow could be preserved with the use of systemic pressor agents, such as midodrine. 30 Indeed, midodrine did not improved OH-related symptoms when the entire cohort was analyzed, however, in our sub-group analysis midodrine improved symptoms in patients who had an increase in seated SBP of at least 15 mm Hg. Atomoxetine, on the other hand, may improve OH-related symptoms not only through its effect on systemic blood pressure but also locally by directly increasing cerebral blood flow.…”
Section: Discussioncontrasting
confidence: 49%
“…Cerebral blood flow could be preserved with the use of systemic pressor agents, such as midodrine. 30 Indeed, midodrine did not improved OH-related symptoms when the entire cohort was analyzed, however, in our sub-group analysis midodrine improved symptoms in patients who had an increase in seated SBP of at least 15 mm Hg. Atomoxetine, on the other hand, may improve OH-related symptoms not only through its effect on systemic blood pressure but also locally by directly increasing cerebral blood flow.…”
Section: Discussioncontrasting
confidence: 49%
“…However, empirical evidence of headache and motion sickness experienced by astronauts in a reduced gravity environment may at least partially be attributed to changes in ICP and cerebral blood flow (Kawai et al 2003). Several studies have investigated and reported variations in both absolute (Matsubara et al 1990) and relative distribution (Warkentin et al 1992) of cerebral blood flow during conditions of rapid postural change. A study by Bosone et al (2004) found that 10 min of 30°head down tilt caused significantly increased arterial pressure at the cranial level, due to the development of a hydrostatic pressure gradient between heart and brain levels.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled studies report increases in standing or sitting BP ranging between 14/7 to 46/27mm Hg in a total of 36 patients with orthostatic hypotension because of autonomic failure (16 with type 2 diabetes mellitus, 9 with multiple system atrophy, 6 with Parkinson's disease and 5 with idiopathic disease). [33,36,37] These results were obtained with fludrocortisone dosages usually between 0.2 and 0.5 mg/day (range 0.1 to 1.0 mg/day). In patients with dysautonomia, midodrine 6.25 to 10mg 4 times daily was more effective than fludrocortisone 0.1 mg/day.…”
Section: Fludrocortisonementioning
confidence: 52%